Opportunity in our Ignorance: Urban Biodiversity Study Reveals 30 New Species and One New Nearctic Record for Megaselia (Diptera: Phoridae) in Los Angeles (California, USA) - Hartop, Emily A.; Brown, Brian V.; Disney, R. Henry L. (Zootaxa, 2015)
An urban biodiversity study sampling primarily from private backyards in Los Angeles, California (USA), reveals the presence of fifty-six species of Megaselia within the first few months of sampling. Thirty of these are described as new to science: M. armstrongorum, M. bradyi, M. brejchaorum, M. carthayensis, M. ciancii, M. creasoni, M. defibaughorum, M. donahuei, M. francoae, M. fujiokai, M. hardingorum, M. heini, M. hentschkeae, M. hoffmanorum, M. hoggorum, M. hoguei, M. isaacmajorum, M. kelleri, M. lombardorum, M. marquezi, M. mikejohnsoni, M. oxboroughae, M. pisanoi, M. renwickorum, M. rodriguezorum, M. sacatelensis, M. seaverorum, M. sidneyae, M. steptoeae, and M. wiegmanae. M. largifrontalis is newly reported from the Nearctic Region. The implications these findings have for future taxonomic work in Megaselia, particularly in urban areas, are discussed.